Participatory integrated agro-climatic services benefits 33,000 farmers in 5 countries of Latin America - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
CCAFS scientists has co-developed and implemented "last-mile" mechanisms to reach directly the farmers providing climate information adapted for its use and allowing it to make a timely decision to mitigate its risk (i.e.,PICSA). In Guatemala's and Honduras's Climate-Smart Village, more than 60% of the farmers have perceived positive effects in yields/production with climate-informed decisions, even in unfavorable rainfall conditions. The effectiveness of PICSA has promoted their scaling out in zones of the Central America dry corridor and other Latinamerica countries.